2017
DOI: 10.1371/journal.pone.0182726
|View full text |Cite
|
Sign up to set email alerts
|

Temperature effects on gene expression and morphological development of European eel, Anguilla anguilla larvae

Abstract: Temperature is important for optimization of rearing conditions in aquaculture, especially during the critical early life history stages of fish. Here, we experimentally investigated the impact of temperature (16, 18, 20, 22 and 24°C) on thermally induced phenotypic variability, from larval hatch to first-feeding, and the linked expression of targeted genes [heat shock proteins (hsp), growth hormone (gh) and insulin-like growth factors (igf)] associated to larval performance of European eel, Anguilla anguilla.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(92 citation statements)
references
References 65 publications
6
83
0
3
Order By: Relevance
“…Recently, Politis et al. () studied the larval stage of European Eels and showed that GH expression was higher at a higher temperature. Here, temperature may not play such a role, as temperatures in northern areas (Grande‐Rivière‐Blanche and Rivière‐Saint‐Jean) are expected to be colder than in the Nova Scotia littoral zone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Politis et al. () studied the larval stage of European Eels and showed that GH expression was higher at a higher temperature. Here, temperature may not play such a role, as temperatures in northern areas (Grande‐Rivière‐Blanche and Rivière‐Saint‐Jean) are expected to be colder than in the Nova Scotia littoral zone.…”
Section: Discussionmentioning
confidence: 99%
“…, ) and in embryonic and larval European Eels (Politis et al. ), and we studied glass eels colonizing rivers previously associated with different American Eel ecotypes (Mersey River on the Atlantic coast [BW/SW ecotype]; Rivière‐Saint‐Jean, Gulf of St. Lawrence [FW ecotype]; and Grande‐Rivière‐Blanche, St. Lawrence estuary [FW ecotype]; Pavey et al. ) and according to their salinity preference (Boivin et al.…”
mentioning
confidence: 99%
“…Gametes from each replicate were then activated using 11.7 ml of activation media, which consisted of reverse osmosis water salted to 36 psu using Red Sea salt (Red Sea International, Eilat, Israel) at 20°C. After 5 min of gamete contact time, the eggs/embryos were transferred into 200‐ml beakers for incubation at 36 psu and 18°C (Politis et al, ). After 4 hr of incubation, embryos from each treatment were transferred into new beakers with filtered UV seawater at 36 psu, supplemented with 50 ppm ampicillin and rifampicin (Sigma‐Aldrich Chemie, Steinheim, Germany; Sørensen et al, ) and kept in a thermal incubator at 18°C (Politis et al, , ).…”
Section: Methodsmentioning
confidence: 99%
“…At present, improved assisted reproductive technologies and in vitro fertilization techniques are implemented to produce viable eggs and hatched larvae (Butts, Sørensen, Politis, Pitcher, & Tomkiewicz, ; Mordenti et al, ; Müller, McEvoy, Tomkiewicz, Politis, & Amigo, ). In addition, controlled laboratory studies have identified optimal environmental conditions for improved early offspring performance, that is light (Politis, Butts, & Tomkiewicz, ), salinity (Sørensen, Butts, Munk, & Tomkiewicz, ) and temperature (Politis et al, , ). Together, this new innovative technology has enabled the production of copious amounts of offspring reaching the first‐feeding stage (Butts, Sørensen, Politis, & Tomkiewicz, ; Sørensen, Tomkiewicz, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fishes are an important, stable and safe protein resource for humans, especially in China where aquaculture is considered an effective method for providing animal proteins (Gui & Zhu, ). During ontogenesis from the oosperm to adulthood, fishes are affected by many threats in the complex water environment, especially in the early stage of development (Bourrachot et al ., ; Du Gas et al ., ; Politis et al ., ). The early stage of development is critical for fishes because the digestive, immune and skeletal systems are incomplete in this stage (Ferraresso et al ., ; Huttenhuis et al ., ; Sahlmann et al ., ).…”
Section: Introductionmentioning
confidence: 97%